Chemical Dimensions of Plastic Wastes and Their Recycling in Environmental Education - Aydinli, Bahattin; Avan, Çağrı (Richtmann Publishing, 2015)
Environment, energy, recycling, sustainability, various footprints that take attentions of all layers of society, are such a key concepts in last decades. These layers are widespread all over the world in terms of the perspectives of academics, politics, economics, mediatics which all try to manipulate societal life respectively to better position. One of the popular debates is usage of plastics and their supposed environmental pollution. This subject also takes the attention of educators and becomes at least one of the subtitles of environmental education research. While, the governmental municipality which has the key responsibility of these issues, academicians make research about these subjects to activate inner faculties of people. Chemical dimension of environmental issues - along with biology, geography and environmental sciences- helps us to take picture of huge problems. In this study, plastics and their recycling were examined as a chemical dimension of environmental education. And also it is accepted that the attitude of the people is a promising sign and indicator to execute the specified behavior. The attitude sometimes supported on triangles of cognitive, affective, and psychomotor skills which covers than all learning behavior of humans. Here, attitudes of sixth grade students were determined about the plastics and recycling in environment. The previously developed attitude scale was applied to 492 primary school students in Kastamonu province of Turkey. The results were analyzed with statistically and evaluated. The factors of the attitude scale and socioeconomic factors were correlated. Some significant differences related with gender residence type obtained. DOI: 10.5901/jesr.2015.v5n1s1p37
Keywords: 13. Climate action; 4. Education; 11. Sustainability; 12. Responsible consumption; 3. Good health